2002
DOI: 10.1128/mcb.22.20.7351-7363.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Neuron-Specific Rai (ShcC) Adaptor Protein Inhibits Apoptosis by Coupling Ret to the Phosphatidylinositol 3-Kinase/Akt Signaling Pathway

Abstract: Rai is a recently identified member of the family of Shc-like proteins, which are cytoplasmic signal transducers characterized by the unique PTB-CH1-SH2 modular organization. Rai expression is restricted to neuronal cells and regulates in vivo the number of postmitotic sympathetic neurons. We report here that Rai is not a common substrate of receptor tyrosine kinases under physiological conditions and that among the analyzed receptors (Ret, epidermal growth factor receptor, and TrkA) it is activated specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
101
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 37 publications
7
101
0
Order By: Relevance
“…Cells expressing 3YF-ShcC become more susceptible to RA-induced apoptosis presumably due to inhibition of the Akt pathway. It has recently been shown that ShcC is physiologically involved in the regulation of the PI3K/Akt pathway as a downstream effecter of the ligand-stimulated Ret receptor in neuroblastoma cells (Pelicci et al, 2002). This study confirms that the survival of NB-39-nu cells is regulated by the signals downstream of ShcC.…”
Section: Discussionsupporting
confidence: 77%
“…Cells expressing 3YF-ShcC become more susceptible to RA-induced apoptosis presumably due to inhibition of the Akt pathway. It has recently been shown that ShcC is physiologically involved in the regulation of the PI3K/Akt pathway as a downstream effecter of the ligand-stimulated Ret receptor in neuroblastoma cells (Pelicci et al, 2002). This study confirms that the survival of NB-39-nu cells is regulated by the signals downstream of ShcC.…”
Section: Discussionsupporting
confidence: 77%
“…28 A recent study also showed that ShcC is a physiological substrate of Ret kinase and that it exerts a prosurvival function in neuronal cells. 40 Although high levels of TrkA expression correlate with a favorable outcome of neuroblastoma patients, 20 TrkA expression was significantly high in NB-39-nu and Nagai, which derive from tumors with a poor prognosis. This discrepancy may also be explained by the overwhelming control of cell survival by ALK kinase in these cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that ShcC elicits these effects through a different kinetic of activation of downstream effector molecules with respect to ShcA. Indeed, ShcC elicits neuronal differentiation via prolonged stimulation of the MAPK (Conti et al, 2001;Pelicci et al, 2002). This behavior is reminiscent of that described in PC12 cells exposed to NGF, where persistent activation of MAPK is required for neuronal differentiation.…”
Section: Driving Proliferation and Differentiation Events In Neural Cmentioning
confidence: 66%
“…This behavior is reminiscent of that described in PC12 cells exposed to NGF, where persistent activation of MAPK is required for neuronal differentiation. On the contrary, ShcC-driven prosurvival effect occurs via recruitment of the PI3K-Akt pathway (Conti et al, 2001;Pelicci et al, 2002), as demonstrated by the fact that its pharmacological or molecular inhibition markedly abolishes this effect. To this respect, ShcC-induced Akt activation was found to cause phosphorylation (with inhibition) of Bad, a proapoptotic member of the Bcl2 family (Conti et al, 2001).…”
Section: Driving Proliferation and Differentiation Events In Neural Cmentioning
confidence: 99%